The Road to Servitization How Product Service Systems Can Disrupt Companies' Business Models - Annarelli, Alessandro; Battistella, Cinzia; Nonino, Fabio (Springer International Publishing : Imprint: Springer, 2019)
The book describes state-of-the-art product service systems, and provides a framework to categorize the knowledge surrounding these systems. It discusses the evolution and spread of the servitization model across industries, and explores its current and most relevant applications in industry. Further, the book highlights the model's strategic value for business and management, operations, and sustainability and shows readers how to enhance service design and implementation. The contributors provide the theory behind servitization as well as the evidence for it, and report practical and industrial lessons learned. Illustrations, charts, and tables effectively guide readers through real-world and potential applications of product service systems, and case studies describing how companies have innovated and developed award winning business models are also included. Moreover, the book exhibits the selection and implementation policies for product service systems in different industrial environments. Providing comprehensive information on the product service system phenomenon, this book is essential reading for researchers and practitioners in the product service and business industries. It is also of interest to students and lecturers in business strategy and service management, as it shows the latest trends shaping the modern contexts in which companies operate.